"Safe Spaces" in Education: Ghettos of Marginalisation and Dominance or Places of Equality and Social Justice?. Issue 2 (August 2015) - Hodkinson, Alan
This article critically analyses the concept of space in generality and specifically the employment of safe space as an educational concept. In addition, by employing Derrida's notion of the arrivant, the article provides an account of the author's frustrations during his analysis of space and of his attempts to reorientate his quantitative writings to ones that are more autobiographical in nature. The argument emplaced in the article is that safe spaces are not safe but in reality are 'warped spaces' where landscapes reveal topographies of despair which mimic modern technological and capitalist development.